Removal of Mannose-Ending Glycan at Asn2118 Abrogates FVIII Presentation by Human Monocyte-Derived Dendritic Cells - Delignat, Sandrine; Rayes, Julie; Dasgupta, Suryasarathi; Gangadharan, Bagirath; Denis, Cécile V.; Christophe, Olivier D.; Bayry, Jagadeesh; Kaveri, Srinivas V.; Lacroix-Desmazes, Sébastien (Frontiers in Immunology, 2020)
The development of an immune response against therapeutic factor VIII is the major complication in hemophilia A patients. Oligomannose carbohydrates at N239 and/or N2118 on factor VIII allow its binding to the macrophage mannose receptor expressed on human dendritic cells, thereby leading to factor VIII endocytosis and presentation to CD4+ T lymphocytes. Here, we investigated whether altering the interaction of factor VIII with mannose-sensitive receptors on antigen-presenting cells may be a strategy to reduce factor VIII immunogenicity. Gene transfer experiments in factor VIII-deficient mice indicated that N239Q and/or N2118Q factor VIII mutants have similar specific activities as compared to non-mutated factor VIII; N239Q/N2118Q mutant corrected blood loss upon tail clip. Production of the corresponding recombinant FVIII mutants or light chains indicated that removal of the N-linked glycosylation site at N2118 is sufficient to abrogate in vitro the activation of FVIII-specific CD4+ T cells by human monocyte-derived dendritic cells. However, removal of mannose-ending glycans at N2118 did not alter factor VIII endocytosis and presentation to CD4+ T cells by mouse antigen-presenting cells. In agreement with this, the N2118Q mutation did not reduce factor VIII immunogenicity in factor VIII-deficient mice. Our results highlight differences in the endocytic pathways between human and mouse dendritic cell subsets, and dissimilarities in tissue distribution and function of endocytic receptors such as CD206 in both species. Further investigations in preclinical models of hemophilia A closer to humans are needed to decipher the exact role of mannose-ending glycans in factor VIII immunogenicity.